The British Society for Rheumatology Biologics Register. (20th October 2005) - Watson, K; Symmons, D; Griffiths, I; Silman, A
Abstract : The British Society for Rheumatology (BSR) established a nationwide register for patients with rheumatological disorders treated with biologic agents. The register is designed as a national prospective study whose primary purpose is to assess long term toxicity from the use of these agents in routine practice. In addition, the data will be capable of addressing the benefits from their use in relation to their toxicity. One specific feature of the BSR register is the recruitment and collection of data from a parallel comparison group, comprising patients with active rheumatoid arthritis treated with conventional disease modifying agents. Both class specific and drug specific analyses of the group treated with biologicals are planned.